Non-inhibitory levels of oxygen during cultivation increase freeze-drying stress tolerance in Limosilactobacillus reuteri DSM 17938 - Rao, Nikhil Seshagiri; Ermann Lundberg, Ludwig; Tomasson, Julia; Tullberg, Cecilia; Brink, Daniel P.; Palmkron, Shuai Bai; van Niel, Ed W. J.; Håkansson, Sebastian; Carlquist, Magnus (Frontiers in Microbiology, 2023)
The physiological effects of oxygen on Limosilactobacillus reuteri DSM 17938 during cultivation and the ensuing properties of the freeze-dried probiotic product was investigated. On-line flow cytometry and k-means clustering gating was used to follow growth and viability in real time during cultivation. The bacterium tolerated aeration at 500 ml/min, with a growth rate of 0.74 ± 0.13 h-1 which demonstrated that low levels of oxygen did not influence the growth kinetics of the bacterium. Modulation of the redox metabolism was, however, seen already at non-inhibitory oxygen levels by 1.5-fold higher production of acetate and 1.5-fold lower ethanol production. A significantly higher survival rate in the freeze-dried product was observed for cells cultivated in presence of oxygen compared to absence of oxygen (61.8 ± 2.4 % vs 11.5 ± 4.3 %), coinciding with a higher degree of unsaturated fatty acids (UFA:SFA ratio of 10 for air sparged vs 3.59 for N2 sparged conditions.). Oxygen also resulted in improved bile tolerance and boosted 5’nucleotidase activity (370 U/L vs 240 U/L in N2 sparged conditions) but lower tolerance to acidic conditions compared bacteria grown under complete anaerobic conditions which survived up to 90 min of exposure at pH 2. Overall, our results indicate the controlled supply of oxygen during production may be used as means for probiotic activity optimisation of L. reuteri DSM 17938.